The role of human and organizational culture in the context of technological change - Zakaria, Norhayati (2001)
The purpose of this paper is to understand the role of three main factors of management: information technology (IT), people, and organizational culture. The first section identifies some managerial challenges, which are inherent in any technological change. Essentially, the change process highlights the interdependent relationship of those three main factors. In the second section, issues of technology, people and organizational culture are discussed in further detail, with some examples from literature. Why people change, what it takes to minimize resistance and how to make change successful are questions that emerge again and again and need further understanding. Consequently, by reviewing the relevant literatures, the authors summarize some of the research with a focus on the decisions made by management when selecting new systems. They investigate those decisions with respect to the three distinct "threads" or factors that directly influence technological change. Lastly, by establishing fundamental propositions, the final two sections provide some implications and conclusions as well as possibilities for future research